2020
DOI: 10.3389/fsufs.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Potential Productivity of Urban Agriculture and Its Impacts on Soil Quality Through Experimental Research on Scale-Appropriate Systems

Abstract: Urban agriculture could play a central role in local and regional food sovereignty in developed countries, but in many cities, a lack of space and competition with other land uses limit production. Options for meaningfully advancing food sovereignty goals include sustainable intensification of existing urban farms and gardens; (2) expansion of production into interstitial and other underutilized spaces undevelopable for other purposes; and (3) expansion of production in protected environments. Observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Because of differences in scale, inputs, and context, agronomic research on commercial farming practices may not provide adequate guidance for the development of alternatives to this perceived standard of management. Instead, experimental research is needed to develop scale‐appropriate best management practices that help gardeners and farmers maximize the ecosystem services of urban food production systems while minimizing their disservices (Taylor, 2020). For example, sites identified with excessive inorganic P values in a soil test would benefit from the use of plant‐based fertility instead of compost‐based materials.…”
Section: Resultsmentioning
confidence: 99%
“…Because of differences in scale, inputs, and context, agronomic research on commercial farming practices may not provide adequate guidance for the development of alternatives to this perceived standard of management. Instead, experimental research is needed to develop scale‐appropriate best management practices that help gardeners and farmers maximize the ecosystem services of urban food production systems while minimizing their disservices (Taylor, 2020). For example, sites identified with excessive inorganic P values in a soil test would benefit from the use of plant‐based fertility instead of compost‐based materials.…”
Section: Resultsmentioning
confidence: 99%
“…These results are comparable with other studies observing dramatic increases in crop productivity because of compost amendments derived from urban waste streams. For example, in one study, researchers observed an 86% increase in marketable vegetable yield after amending soil with a local yard waste compost (Taylor, 2020) and in another, compost‐amended plots on urban farms produced eight to ten times more tomato fruit (Beniston et al., 2016). While these results are exciting and validate reports by our local growers of the value of leaf mold compost for urban farms, not all compost applications are likely to result in such dramatic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…There will be around 130 million individuals who are experiencing severe food insecurity by the end of the year 2020. The seriousness of the situation is clearly shown by the present global food crisis and the consequences that it has brought about [30].…”
Section: Effect Of Urban Farming On Different Aspectsmentioning
confidence: 99%